Petrogenesis of the volcanic suite of Bouvetøya (Bouvet Island), South Atlantic - Prestvik, Tore; Goldberg, Steven; Goles, Gordon G. (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1999)
Whole rock and mineral compositions of volcanic rocks collected during the Norwegian Polarsirkel expedition (1978/79) to the volcanic istand of Bovetøya (close to the Bouvet Triple Junction) are discussed and compared with previously published data from the island. The rock types, hawaiite, benmoreite, and peralkaline trachyte and rhyolite (comendite) are related to each other by crystal fractionation processes. The trace element and radiogenic isotope signatures displayed by the Bouvetøya rocks are those of a moderately enriched oceanic island suite. On several isotope plots Bouvetøya rocks fall on or close to mixing lines between the euriched EM-l and HIMU mantle components. Mixing between depleted morb mantle (DMM) and euriched components is not likely. Thus, Bouvetøya displays a typical plume signature.
Publisher: [Routledge]
Keywords: Bouvetøya; M/V Polarsirkel; NARE 1978/79; geokjemi; geologi; petrologi

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Breeding biology and diet of pintado petrels Daption capense at Bouvetøya during the summer of 1996/97 - Huyser, Onno; Dyer, Bruce M; Isaksen, Kjell; Ryan, P; Cooper, J (Commission for the Conservation of Antarctic Marine Living Resources, 1997)
Pages: [13 s.] Publication Title: Working Group on Ecosystem Monitoring and Management Place: Hubbs-Sea World Research Institute, San Diego, USA
Keywords: Bouvetøya; ornitologi; petreller; reproduksjon; zoologi

Establishment of a CEMP-monitoring program at Bouvetøya - Isaksen, Kjell; Bakken, Vidar; Gjertz, Ian; Mehlum, Fridtjof (Commission for the Conservation of Antarctic Marine Living Resources, 1997)
Pages: [9 s.] Publication Title: Working Group on Ecosystem Monitoring and Management Place: Hubbs-Sea World Research Institute, San Diego, USA
Keywords: Bouvetøya; forskningsstasjoner; overvåking; pingviner; seler; zoologi

Preliminary results from CEMP monitoring of Antarctic fur seals, chinstrap penguins and macaroni penguins at Bouvetøya 1996/97 - Isaksen, Kjell; Hofmeyr, Greg J G; Dyer, Bruce M; Næstvold, Alf; Mehlum, Fridtjof; Gjertz, Ian; Bakken, Vidar; Huyser, Onno (Commission for the Conservation of Antarctic Marine Living Resources, 1997)
Pages: [26 s.] Publication Title: Working Group on Ecosystem Monitoring and Management Place: Hubbs-Sea World Research Institute, San Diego, USA
Keywords: Bouvetøya; forskningsstasjoner; overvåking; pingviner; seler; zoologi

Studies of seabirds and seals at Bouvetøya 1996/97 - Isaksen, Kjell; Hofmeyr, Greg; Dyer, Bruce M; Huyser, Onno; Næstvold, Alf (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Bouvetøya; NARE 1996/97; fugler; ornitologi; seler; zoologi

Fugle-og selundersøkelser på Bouvetøya i desember/januar 1989/90 - Bakken, Vidar (Norsk Polarinstitutt, 1991)
Publication Title: Meddelelser
Keywords: Bouvetøya; biologi; fugler; fugleregistreringer; ornitologi; pingviner; seler; zoologi

Distribution of selenium binding proteins in liver from two species of penguins from Bouvetøya - Norheim, Gunnar; Mehlum, Fridtjof; Bech, Claus; Moksnes, Milica T. (Polar Research, 1991)
Chinstrap penguin Pygoscelis antarctica and macaroni penguin Eudyptes chrysolophus were collected at Bouvettfya in the south Atlantic. The average hepatic selenium levels for the two species were 6.6 ± 2.9 and 23.6 ± 3.4 ng/g wet weight (P < 0.001), respectively. The total hepatic glutathione peroxidase (GSH-Px) activity in the two species was 629 ± 58 and 838 ± 88 u.kat/kg (P < 0.001), respectively. The average selenium dependent GSH-Px activity was 96 ± 3.2% of the total activity. All selenium was present in the cytosol. The selenium binding compounds were separated on Sephadex G-75 into three fractions, a high molecular weight fraction, a metallothionein fraction, and a third non-protein selenium containing fraction. There seems to be an agreement between the amount of selenium recovered in the first fraction and the GSH-Px activity. In chinstrap and macaroni penguins, the percentage of hepatic selenium recovered in the third non-protein fraction was 83 ± 2.6 and 94 ± 1.1% (P < 0.001), respectively.
Keywords: Bouvetøya; NARE 1984/85; farmakologi; miljøgifter; pingviner; zoologi

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

Frimerkespalten - Tandberg, Arne Ingar (Skipet, 1990)
Keywords: Antarktis; Bouvetøya; ekspedisjoner; filateli; historie; logistikk; skip

Pingvinfamilien - Sømme, Lauritz; Kalas, Sybille (Cappelen, 1989)
Keywords: Bouvetøya; fugler; pingviner

Norway's polar territories - Barr, Susan (Aschehoug, 1987)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Peter I. Øy; geografi; geologi; historie; polarområdene; polarpolitikk

Botany of Bouvetøya, South Atlantic Ocean. II. The terrestrial vegetation of Bouvetøya - Engelskjøn, Torstein (Polar Research, 1987)
Keywords: Bouvetøya; botanikk; forskning; planter

Bryophytes of Bouvetøya - Bell, Graham B; Blom, Hans H (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

General outline of the botanical investigations on Bouvetøya - Engelskjøn, Torstein (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner

Zonality of climate and plant distributions in some Arctic and Antarctic regions - Engelskjøn, Torstein (Norsk Polarinstitutt, 1986)
Publication Title: Norsk Polarinstitutt. Rapportserie
Keywords: Bouvetøya; Dronning Maud Land; botanikk; klima; planter; polarområdene

Phytogeographical relations of the cryptogamic flora of Bouvetøya - Engelskjøn, Torstein; Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; lav

A quantitative analysis of the behaviour of the Chinstrap penguin Pygoscelis antarctica and Macaroni penguin Eudyptes chrysolophus on Bouvetoya during the late incubation and early nestling periods - Haftorn, Svein (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; pingviner; zoologi

Macrolichens of Bouvetøya - Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

The supralittoral, freshwater and terrestrial algal vegetation of Bouvetøya - Klaveness, Dag; Rueness, Jan (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; alger; botanikk

Hydrolysis of proteins by peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. The hydrolysis of casein by peptide hydrolases of Antarctic krill, E. superba, has been 2. The peptide hydrolases studied included trypsin-like enzymes, carboxypeptidase A-type of enzymes, carboxypeptidase B-type of enzymes, and an aminopeptidase isolated from Antarctic krill. 3. The trypsin-like enzymes seemed to play a decisive role in the degradation of casein, whereas the carboxypeptidase A, carboxypeptidase B and the aminopeptidase had limited effect when acting on casein alone. When combined with the trypsin-like enzymes, the exopeptidases effected enhanced release of amino acids from the protein. 4. Based on the pattern of amino acids relased from casein by a crude extract of krill, and by the isolated peptide hydrolases either alone or in combination, it is concluded that the purified peptide hydrolases examined comprise the major enzymes responsible for the autoproteolytic activity of krill at neutral- to weakly alkaline pH.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

On the purification and characterization of exopeptidases from Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. Two carboxypeptidase-A type of enzymes and two carboxypeptidase-B type of enzymes effecting hydrolysis of Hipp-l-Phe and Hipp-l-Arg respectively, have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. In addition an aminopeptidase has been partly purified. 2. The carboxypeptidases had mol. wts of 27,000 (carboxypeptidase A) and 31,000 (carboxypeptidase B). 3. Carboxypeptidase A exhibited a broad pH optimum with a maximum at pH 5.5–6.5, whereas carboxypeptidase B had a more narrow pH-optimum with a maximum at pH 7. The aminopeptidase had an optimum at about pH 8.7. 4. The carboxypeptidases were inhibited by the chelating agent 1,10-phenanthroline.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Crustose lichens of Bouvetøya - Øvstedal, Dag Olav (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Lichencolous ascomycetes from Bouvetøya - Øvstedal, Dag Olav; Hawksworth, David L (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Lamprospora miniatopsis Spooner, a bryophilous discomycete from Bouvetøya - Schumacher, Trond (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

Terrestrial arthropods of Bouvetøya - Sømme, Lauritz (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; forskning; midder; miter; virvelløse dyr

Suksess i syd: utvidet forskning i Antarktis (Forsvarets forum, 1985)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; logistikk

Geodetic-topographic measurements in Dronning Maud Land and on Bouvetøya - Eiken, Trond; Svendsen, Knut (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; geodesi; målinger; topografi

På ekspedisjon til Sørpolen - Moberg, John (Norsk barneblad, 1985)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; ekspedisjoner; geofysikk; glasiologi; teknologi

Geology of Gjelsvikfjella and western Mühlig-Hofmannfjella - Ohta, Yoshihide; Tørudbakken, Bjøn (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; geologi

On the purification and characterization of three anionic, serine-type peptide hydrolases from antarctic krill, Euphausia Superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. Three enzymes effecting hydrolysis of TAME have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. 2. The enzymes had molecular weights of 30,000 (Enzyme I), and 31,000 (Enzymes II and III), respectively, as estimated from SDS-PAGE. 3. pH-optima of about 8.2 were observed for all three enzymes. 4. The enzymes were inhibited by phenyl methyl sulphonyl fluoride (PMSF), tosyl lysyl chloromethyl ketone (TLCK) and soybean trypsin inhibitor (SBTI), whereas tosyl phenyl chloromethyl ketone (TPCK) had no effect on the activity. 5. The enzymes were stable at neutral pH, and only slowly inactivated at highly alkaline pH. Low pH rapidly inactivated all three enzymes. 6. Enzyme I liberated amino acids from casein, whereas Enzymes II and III did not; the latter two being true endopeptidases which effected enhanced amino acid production from casein when mixed with Enzyme I.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Peptide hydrolases of Antartic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. A survey has been made of the peptide hydrolase activities occurring in Antarctic krill, Euphausia superba. 2. A major protein hydrolyzing activity in the pH range of 6–8, and a minor activity at pH 3–4, were detected. 3. Temperature optima of approx. 50°C and 35–40°C, respectively were determined for the neutral and acid peptide hydrolases. 4. Trypsin-like activity, as well as carboxypeptidase A-, carboxypeptidase B-, and aminopeptidase activity were detected in extracts of krill. 5. Considerable variation in total hydrolase activity was observed in different catches of E. superba obtained from the same area. 6. The pattern of release of amino acids during autolytic breakdown of krill proteins was very similar in catches of krill exhibiting considerable differences with respect to total peptide hydrolase activity.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Biokjemiske studier over antarktisk krill - Ellingsen, Trond E; Norges tekniske høgskole Institutt for teknisk, biokjemi (Institutt for teknisk biokjemi, 1982)
Volume: nr.: [262] ISBN: 8272450100
Keywords: Bouvetøya; Sørishavet; Weddellhavet; biokjemi; krill; lipider; lyskreps; marinbiologi

A microearthquake survey of Bouvet Island, South Atlantic - Kristoffersen, Yngve; Bungum, Hilmar (Tectonophysics, 1982)
A microearthquake survey carried out during the 1978–1979 Norwegian Antarctic Research Expedition indicates that only minor seismic activity is associated with the Bouvet volcano.
Keywords: Bouvetøya; NARE 1978/79; geofysikk; seismologi; vulkaner

Mercury and persistent chlorinated hydrocarbons in antarctic birds from bouvetøya and dronning maud land - Norheim, Gunnar; Sømme, Lauritz; Holt, Gunnar (Environmental Pollution Series A, Ecological and Biological, 1982)
The concentrations of DDE, PCB, hexachlorobenzene (HCB) and mercury were determined in samples from chinstrap penguin Pygoscelis antarctica, macaroni penguin Eudyptes chrysolophus, snow petrel Pagodroma nivea, Cape pigeon Daption capense, southern fulmar Fulmarus glacialoides, south polar skua Catharacta maccormicki and brown skua Catharacta lonnbergi. The birds were taken in central parts of Vestjella in Dronning Maud Land in February 1977 and at Bouvetøya in the South Atlantic in February 1977 and January 1979. Low levels of DDE, PCB and HCB were found in the two species of penguins, snow petrel, Cape pigeon and southern fulmar, while significantly higher levels were found in south polar and brown skua. The lowest mercury levels were found in the two penguin species and snow petrel. Cape pigeon, southern fulmar and south polar skua form an intermediate group, while the highest mercury levels were found in brown skua. It is assumed that there is a connection between the present findings and the migration pattern of the different birds. The results seem to be in agreement with previous investigations.
Keywords: Bouvetøya; Dronning Maud Land; forurensning; fugler; miljøgifter; ornitologi; økologi

Basic volcanic rocks and tectonic setting. A discussion of the Zr-Ti-Y discrimination diagram and its suitability for classification purposes - Prestvik, Tore (Lithos, 1982)
Keywords: Bouvetøya; forskning; geologi; tektonikk; vulkaner

Analysis of wave measurements at Bouvetøya - Arntsen, Øivind A; Snuggerud, John (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; ekspedisjoner; forskning; oseanografi

The seismicity of the Bouvetøya region - Bungum, Hilmar; Kristoffersen, Yngve; Nilsen, Alf K. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; seismologi; vulkaner

Terrestrial vegetation of Bouvetøya : a preliminary account - Engelskjøn, Torstein (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; botanikk; ekspedisjoner; forskning

Hydrographic surveying around Bouvetøya - Fjørtoft, Jon H (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; hydrografi; oseanografi

Measurements of ocean current and bottom pressure near Bouvetøya, January–March 1979 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; havstrømmer; oseanografi

Geodetic determination of Bouvetøya - Fossum, Bjørn A (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; geodesi

A census of penguins and seals on Bouvetøya - Haftorn, Svein; Sømme, Lauritz; Gray, John S (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; pingviner; seler; zoologi

New map of Bouvetøya - Helle, Sigurd G (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; M/V Polarsirkel; NARE 1976/77; NARE 1978/79; geodesi

The glaciers of Bouvetøya - Orheim, Olav (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; glasiologi; isbreer

Geology of Bouvetøya, South Atlantic - Prestvik, Tore; Winsnes, Thore S. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; geologi; vulkaner

Supercooling in two Antarctic arthropods from Bouvetøya - Sømme, Lauritz (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Krill off Bouvetøya and in the southern Weddell Sea with a description of larval stages of Euphausia crystallorophias - Fevolden, Svein Erik (Sarsia, 1980)
In the austral summer 1978/79 samples of krill were taken off Bouvetøya and in the southern Weddell Sea. Off Bouvetøya Euphausia superba Dana was the dominant species, but the population pattern indicates that the individuals found there were expatriates from other areas. For the first time larvae of E. superba were found in significant amounts in the southern Weddell Sea. Except from shallow water and the most southern position, they were equal in abundance to the larvae of E. crystallorophias Holt & Tattersall. Larval stages of the latter are described as is the successive spawning that takes place among the three species of krill found in the southern Weddell Sea.
Publisher: Taylor & Francis
Keywords: Bouvetøya; NARE 1978/79; Weddellhavet; dyreplankton; krill; plankton; zooplankton

Investigations on krill (Euphausiacea) sampled during the Norwegian Antarctic Research Expedition 1976–1977 - Fevolden, Svein Erik (Sarsia, 1979)
Krill was sampled in the Weddell Sea, farther south than ever before, and off Bouvet-öya. Five species were found: Euphausia superba, E. crystallorophias, E. frigida, E. triacantha, and Thysanoessa macrura. E. superba and E. crystallorophias were the most abundant species north and south of 74° S respectively. Length frequency analyses suggest that E. superba from the inner Weddell Sea takes three years to reach maturity. This population differed in several aspects from the populations farther north. E. crystallorophias and T. macrura were registered south to 77°45′ S, the southernmost localisation investigated. The material gives no clear evidence whether these species take one or two years to reach maturity. Their spawning activity seems to start earlier in the season than for E. superba. E. frigida and E. triacantha were only-found off Bouvetöya. Continuous echosounder recordings revealed that the total abundance of krill in the southern parts of the Weddell Sea was low, as was also the abundance on the route between the South Orkney Islands and Dronning Maud Land.
Publisher: Taylor & Francis
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; Sør-Orknøyene; Sørishavet; Weddellhavet; dyreplankton; krill; plankton; zooplankton

An eruptional model for recent lava flow on Bouvetøya, South Atlantic Ocean - Furnes, Harald; Løvlie, Reidar (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi

Palaeomagnetism and morphology of lava(s) at Cape Meteor, Bouvetøya - Løvlie, Reidar; Furnes, Harald (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; geologi; vulkaner

Results from Norwegian Antarctic research 1974-1977 - Polarinstitutt, Norsk (1978)
Publication Title: Norsk Polarinstitutt. Skrifter
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner

Cold-Hardiness of Cryptopygus antarcticus (Collembola) from Bouvetøya - Sømme, Lauritz (Oikos, 1978)
Cryptopygus antarcticus Willem were extracted from samples of mosses collected at Bouvetøya during the Norwegian Antarctic Expedition in February 1977. The body length of the collembolans from these samples ranged from 225 to 1125 μm. The collembolans had average supercooling points between -24° and -26°C. Acclimation at -5°, 0° and 12°C for various time intervals had no significant effect on their ability to supercool. Glycerol was not found in specimens acclimated at -5° and 0°C. All specimens were killed by freezing at temperatures in the range of their supercooling points. Chill-coma temperatures of the collembolans were between -2° and -7°C.
Keywords: Bouvetøya; NARE 1976/77; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Meteorological observations from Bouvetøya - Vinje, Torgny E (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1978)
Keywords: Bouvetøya; meteorologi

Weather and tide observations at Bouvetøya - Vinje, Torgny E (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi; observasjoner; oseanografi

Observations on birds and seals at Bouvetøya - Fevolden, Svein Erik; Sømme, Lauritz (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Bouvetøya; ekspedisjoner; fugler; pingviner; zoologi

The geology and petrology of Bouvetøya, south Atlantic Ocean - Imsland, Pall; Larsen, Jørgen Gutzon; Prestvik, Tore; Sigmond, Ellen M (Lithos, 1977)
Keywords: Bouvetøya; forskning; geologi; petrologi

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Pages: 154-160 Publication Title: El desarrollo de la Antártica Place: Punta Arenas, Chile
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium

Bouvetøya proclaimed a nature reserve (Polar Record, 1972)
Publisher: Cambridge University Press
Keywords: Bouvetøya; lovgivning

Forskrift om fredning av Bouvetøya med tilliggende territorialfarvann som naturreservat - miljødepartementet, Klima- og (Lovdata, 1971)
Volume: 1971-12-17-9 Place: Oslo
Keywords: Bouvetøya; jus; miljøvern; naturvern

Norske oppdagelser og rettigheter i Antarktis. Vurdering av norske territoriale og andre rettigheter i Arktis og Antarktis (En oversikt over fiske, fangst og norske polarinteresser, 1967)
Keywords: Antarktis; Bouvetøya; Norge; ekspedisjoner; fiske; hvalfangere; hvalfangst; interesser; internasjonal; oppdagelsesreiser; politikk

Fra et besøk på Bouvetøya - Lunde, Torbjørn (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Bouvetøya; geologi; glasiologi

Besøk på Bouvetøya i 1958 og 1966 (Bouvetøya twice visited) - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1965, 1965)
Keywords: Bouvetøya; ekspedisjoner; geologi; observasjoner; topografi

Nyere iakttagelser over fuglelivet på Bouvetøya - Heintz, Natascha (Norsk Polarinstitutt. Årbok 1961, 1962)
I «Informasjons-bulletin for den sovjetiske Antarktisekspedisjon», nr. 13, (1959) har G. A. SOLJANIK publisert en liten artikkel om fuglelivet på Bouvetøya. Da forfatteren har vært i land nær Kapp Circumcision hvor det tidligere, så vidt jeg kan bringe i erfaring, ikke har vært foretatt noen landing, kan det kanskje være av interesse å referere noen av de opplysningene han kommer med, ikke minst da det på en interessant måte utvider vårt kjennskap til fuglefaunaen på denne ugjestmilde øya.
Keywords: Bouvetøya; fugler; ornitologi

Fugl i norske biland. - 2. Bouvet-øya - Holgersen, Holger (Sterna, 1960)
Publisher: Museet Place: Stavanger
Keywords: Bouvetøya; fugler; ornitologi; zoologi

Antarctic pelecypods - Soot-Ryen, Tron (Dybwad, 1951)
Publication Title: Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq., instituted and financed by consul Lars Christensen
Keywords: Bouvetøya; Peter I. Øy; bivalvia; bløtdyr; ekspedisjoner; forskning; muslinger; zoologi

Sydishavet: Blad 2 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1950)
Place: Sandefjord
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; geografi; kartlegging

Some new and remarkable leeches from the Antarctic seas - Brinkmann, August (Dybwad, 1948)
Publication Title: Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq., instituted and financed by consul Lars Christensen
Keywords: Bouvetøya; Norvegia ekspedisjonen; Sørishavet; fisker; igler; marin biologi

Die südpolaren Gebiete - Smedal, Gustav (Souveränitätsfragen der Polargebiete : norwegische Interessen in den Eismeeren, 1943)
Keywords: Antarktis; Bouvetøya; Norge; Peter I. Øy; internasjonal; polarområdene; politikk; rett

Oppdeling av polatraktene - Hoel, Adolf (Norge i Ishavet, 1941)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; internasjonal politikk; polarområdene

Bouvet-Insel - Engelmann, Gerhard (Geographische Zeitschrift, 1940)
Publisher: Franz Steiner Verlag
Keywords: Bouvetøya; geografi; historie

The Norwegian sector of the Antarctic (The Geographical Journal, 1939)
Keywords: Bouvetøya; internasjonal politikk; rett

Sydishavet - Kong Haakon VII Hav (Blad 1) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; Thorshammer ekspedisjon; geografi; kartlegging

Sydishavet (Blad 1) (Hvalfangernes Assuranceforening, 1936)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; geografi; kartlegging

Bunnen av Weddellhavet (Hvalfangernes Assuranceforening, 1935)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1935)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

The waters of the Atlantic Antarctic Ocean - Mosby, Håkon (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1934)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; hydrografi; oseanografi; strømmer; vannmasser

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1933)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

The sea-surface and the air - Mosby, Håkon (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1933)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; havoverflaten; hydrografi; meteorologi

Antarktische und antiboreale Polychaeten nebst einer Hirudinee - Augener, H (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1932)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; forskning; havbørsteormer; marin biologi; polychaeter; zoologi

Norvegia-ekspedisjonen 1930-1931 (Norges geografi oppmåling, 1931)
Pages: 5 kart Place: [S.l.]
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Lov om Bouvet-øya, Peter I's øy og Dronning Maud Land m.m. (bilandsloven) (Lovdata, 1930)
Volume: 1930-02-27-3 Place: Oslo
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; jus; lovgivning

The Antarctic (The Geographical Journal, 1930)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Bouvetøya; Christen Christensen; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; Peter I. Øy; kartlegging; oppdagelsesreiser

Våre polarflyverferder i nord og syd - Arnesen, Odd (Til veirs på norske vinger : av flyvningens historie i Norge, 1930)
Keywords: Antarktis; Bouvetøya; Finn Lützow; Hjalmar Riiser Larsen; Holm; Nordmenn; Norge; Norvegia ekspedisjonen; biografier; historie; kartlegging; luftfart

Antarctic discoveries - Brown, R N Rudmose (Scottish Geographical Magazine, 1930)
Publisher: Routledge
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; kartlegging; oppdagelsesreiser

Antarctic and Subantarctic Actiniaria - Carlgren, Oskar (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; forskning; marin biologi; sjøanemoner; sjøroser

Forskrift om Bouvet-øya - Justisdepartementet (Lovdata, 1930)
Volume: 1930-09-19-3663 Place: Oslo
Keywords: Bouvetøya; jus

Den Tredje »Norvegia«-Ekspedisjon 1929—1930 - Riiser-Larsen, Hjalmar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1930)
Publisher: Routledge
Keywords: Bouvetøya; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; geografi; kartlegging

Euphasiacea : with notes in their biogeography and development - Rustad, Ditlef (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjonen; forskning; krepsdyr; krill; marin biologi; plankton; zoologi

Echinodermata from the Palmer Archipelago, South Shetland, South Georgia and the Bouvet Island : with description of new species of the moluscan genus Montacutas - Grieg, James A (Dybwad, 1929)
Publication Title: Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I
Keywords: Bouvetøya; biologi; ekspedisjoner; forskning; marinbiologi; pigghuder; virvelløse dyr

On the geology and physiography of some Antarctic and Sub-Antarctic islands : with notes on the character and origin of fjords and strandflats of some northern lands - Holtedahl, Olaf (Dybwad, 1929)
Publication Title: Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi

Die norwegische Bouvetinsel - Sachse, Walter (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1929)
Publisher: Perthes Place: Gotha
Keywords: Bouvetøya; Norvegia ekspedisjoner; geografi; oppdagelsesreiser

The "Norvegia"-expedition and Bouvet Island - Aagaard, Bjarne (Norges Handels og Sjøfartstidende, 1928)
Keywords: Antarktis; Bouvetøya; Lars Christensen; Norvegia ekspedisjonen; ekspedisjoner; geografi; historie; internasjonal; politikk; rett

Bouvet-øen og "Norvegia"-ekspedisjonen 1927-1928 - Mosby, Håkon (Naturen, 1928)
Place: Bergen
Keywords: Bouvetøya; Norvegia ekspedisjonen; meteorologi; oppdagelsesreiser

Trekk av Sydishavets dyreliv - Olstad, Ola (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Publisher: Routledge
Keywords: Antarktis; Bouvetøya; Lars Christensen; Norvegia ekspedisjoner; Peter I. Øy; dyreliv; forskning; zoologi